Clofarabine induces tumor cell apoptosis, GSDME-related pyroptosis, and CD8+ T-cell antitumor activity via the non-canonical P53/STING pathway - Jing Chen; Jie Wu; Xiang Chen; Qian Tao; Nian Liu; Cong Peng; Can Lu; Qiuqiu Li (Journal for ImmunoTherapy of Cancer)
Background Clofarabine (Clo) is a Food and Drug Administration (FDA)-approved drug for the treatment of acute lymphoblastic leukemia; however, its effects on solid tumors remain largely unknown.Methods In vitro and in vivo experiments have demonstrated the cytotoxic effects of Clo on melanoma and lung cancer. The molecular mechanisms of Clo-induced tumor cell death were analyzed using western blotting, ELISA, reverse transcription-PCR, immunofluorescence, co-immunoprecipitation (CO-IP), short hairpin RNA, co-culture, chromatin immunoprecipitation, and flow cytometry. Clinical data sets were used to analyze the correlation between stimulator of interferon genes (STING)-NFκB signaling and immune infiltration.Results In this study, Clo significantly reduced the growth of melanoma and lung cancer cells. Furthermore, Clo treatment induced GSDME-mediated pyroptosis. Most importantly, Clo administration dramatically increased the cytotoxic activity of CD8+ T cells in vitro and in vivo. Mechanistically, the administration of Clo induced the interaction of P53 with STING, which activated the non-canonical STING-NFκB pathway; consequently, NF-κB directly bound to the promoter regions of its target genes, including CCL5, CXCL10, HLAs and BAX. This resulted in apoptosis, pyroptosis, and immunogenic cell death in tumor cells by Clo. Furthermore, Clo-induced GSDME-mediated pyroptosis partly assists in activating T cell immunity via CCL5 and CXCL10. The non-canonical STING-NF-κB pathway is the crucial signaling pathway that initiates and links apoptosis, pyroptosis, and immunogenic cell death.Conclusions Our study is the first to show that Clo, an FDA-approved drug, induces tumor cell apoptosis, GSDME-related pyroptosis, and CD8+ T-cell antitumor activity via the non-canonical P53-STING-NF-κB signaling pathway, providing a novel strategy for the clinical therapy of melanoma and lung cancer.